Risk factors of invasive cervical cancer in Morocco - Meftah El Khair, M; Ait Mhand, R; El Mzibri, M; Ennaji, M M (Cellular and Molecular Biology, 2009)
It is now well established that infection with oncogenic human papillomavirus (HPV) types is the necessary cause of cervical cancer (CC) and its immediate precursor cervical intraepithelial neoplasia 3. However, HPV infection alonemay not be sufficient to cause CC, and other exogenous and endogenous factors may exist that, in conjunction with HPV, influence the risk of progression from cervical HPV infection to CC. In this chapter, we review the evidence for the role of parity, oral contraceptive (OC) use, and tobacco smoking in CC. In this study, molecular detection of HPV by PCR using consensus primers MY09/MY11 able to amplify the L1 gene present in all types of HPV from fresh frozen biopsies showed that the virus is present in 88% (99/113) of cases. The viral typing, carried out on HPV positive cases through hybridization using specifics probes MY14, WD74, WD126, MY16, MY70 and MY115 which correspond respectively to HPV 16, 18, 31, 33, 45 and 59 has revealed the prevalence of HPV 16 and 18 respectively with 65% (64/99) and 44.4% (44/99). Several combinations of double and multiple infections were also observed. Another part of this work has been devoted to the study of risk factors associated with the development of cancerous cervical lesions. The study is based on a questionnaire during the sampling and also on data collected from clinical records and records of hospital patients.